Peran Pemerintah Dalam Pelayanan Publik Atas Keterbukaan Informasi Perekaman KTP-El Di Kantor Kecamatan Medan Baru - Lubis, Fachrizaly; Jamilah, Jamilah; Saputra, M Yusrizal Adi (JUNCTO: Jurnal Ilmiah Hukum, 2024)
Electronic KTP is a population document that contains a security / control system both in terms of administration and information technology based on the national population database. The type of research used is normative juridical and the nature of the research used is descriptive analytical. Data collection techniques are using 2 (two) methods, namely library research and field research, data analysis is done qualitatively. The results of the research in 2011 the population of Medan Baru Subdistrict is estimated to have reached 57,962 people, the processing of KTPs is recorded and documented in a special agenda book for Electronic KTPs, it is absolutely necessary to have valid population data and already have NIK and recording of pass photos, signatures, fingerprints, and iris of residents, the results of the discussion of Law Number 24 of 2013 in Article 1 number 21 concerning population administration information systems so that Electronic KTPs contain security codes and electronic records as a means of verification and validation of a person's identity data.